Sustainability of maize (Zea mays)-wheat (Triticum aestivum) cropping system under legumes intercropping and effect of nitrogen level on light distribution, soil temperature and crop productivity - NARESH, R K; SINGH, S P; KUMAR, PARVINDER; SINGH, B; SINGH, P K; CHAUHAN, PANKAJ; RATHORE, R S (The Indian Journal of Agricultural Sciences, 2014)
Agriculture designs for cropping system with legume intercropping for increased resource use efficiency profitability, productivity and reduced adverse environmental impact are urgently required. A three years field experiment consisting of six cropping treatments applied during both seasons was conducted during 2008-09 to 2010-11 to study the effect of nitrogen and legumes intercropping with maize (Zea mays L.) for sustainability of maize-wheat (Triticum aestivum L.) cropping system. Results indicate that the photosynthetic active radiation had highest values at noon reaching nearly 1940 µmol/m2/s for maize and 1620 µmol/m2/s for intercropped legumes. Intercropping can increase light interception, shading and reduce water evaporation as compared to sole maize. Maize intercropped had higher values of stomatal condutance and leaf temperature than sole crop. The grain yield and yield attributing characters of wheat crop increased significantly under intercropping treatments over respective check. Wheat yield significantly increased up to 160 kg N/ha. However, there was no significant increase in yield of maize beyond 120 kg N/ha.Sole maize-wheat rotation showed a decline in soil organic carbon by 3.7%,while blackgram and cowpea intercropping with maize in paired rows (2:2 row ratio) followed by wheat increased contents of percent organic carbon in soil as 0.63 and 0.67 respectively, compared to initial values of 0.54 percent. Plots treated with intercrops/FYM during the rainy season sustained the wheat yield while the check plot showed a decline in wheat yield by 4-9%.